The Effectiveness of Snowball Throwing Learning Method on the Living Things Classification Material to the Studentâs Learning Interest and Outcomes. - Fitriani, Kasih; Martuti, Nana Kariada Tri; Utami, Nur Rahayu (Journal of Biology Education, 2018)
The purpose of this research is to develop an interactive multimedia based PBL that suitable for learning human excretory system, and to analyze its effectiveness to increase the learning outcomes and student activity. The research design, was Research and Development (R&D). This research has carried out in SMP N 1 Batang, with class VIII C as subject of research. The class selection was using purposive sampling technique. The results showed that interactive multimedia based PBL developed was valid according to experts as validator. Interactive multimedia based PBL human excretory system effective to be used in learning human excretory system, and student can improve their activity and score in the test. It can be concluded that the learning media of interactive multimedia based PBL is effective for human excretory learning and increase learning outcome.The purpose of this research is to develop an interactive multimedia based PBL that suitable for learning human excretory system, and to analyze its effectiveness to increase the learning outcomes and student activity. The research design, was Research and Development (R&D). This research has carried out in SMP N 1 Batang, with class VIII C as subject of research. The class selection was using purposive sampling technique. The results showed that interactive multimedia based PBL developed was valid according to experts as validator. Interactive multimedia based PBL human excretory system effective to be used in learning human excretory system, and student can improve their activity and score in the test. It can be concluded that the learning media of interactive multimedia based PBL is effective for human excretory learning and increase learning outcome.